Предмет: Алгебра,
автор: Аноним
срочно!!!!!!!даю 79 балов
Приложения:
Ответы
Автор ответа:
0
Ответ:
Объяснение:
преобразуем выражение, 25p^2-30pq+9q^2-25p^2-10pq-q^2=-40pq+8q^2=-40*(-2)*1+8*1=88
(5a-4)^2-36, a=0, 1, 2 - не подходят, подставим а=3, тогда (5*3-4)^2-36=
=(15-4)^2-36=81-36=45 и 45: 5. отв а=3
Похожие вопросы
Предмет: Математика,
автор: Samuray678
Предмет: Алгебра,
автор: sonyapanamera
Предмет: Українська мова,
автор: igorsenik777
Предмет: Геометрия,
автор: Alen202
Предмет: Математика,
автор: САШАКРУТКА3
1) мне лень
2) уже есть решение, которое я проверил
Не огорчайся :D